PENGARUH PENGUNGKAPAN RISIKO TERHADAP BIAYA MODAL EKUITAS DAN KINERJA BANK - Cicilia Chrissanti Ardhi Utami; Dwi Ratmono (Diponegoro Journal of Accounting, 2018)
This study aims to examine the effect of risk disclosure on cost of equity capital. In addition, this study also aims to  examine the effect of risk disclosure on performance. The first hypothesis of the study is risk disclosure has negative effect on cost of equity capital. The second hypothesis of the study is risk disclosure has positive effect on performance. The population in this study is banking companies list on the Indonesia stock exchange in 2011-2016. The sampling method is using purposive sampling. A total observation used in the study was 156 banking companies. Analytical technique used for testing the hypothesis in this study is multiple regression analysis by Eviews 9.The results of analysis couldn’t support the hypothesis before because risk disclosure has no effect on cost of equity capital. In addition, the result of  the second hypothesis analysis also showed that risk disclosure has no effect on performance.